Analisis Determinan Pengangguran: Studi Kasus Negara Asean-6 (Indonesia, Filipina, Laos, Malaysia, Vietnam, Thailand) - Salsabilla, Alda Shakira; Kusuma, Hendra (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2024)
Unemployment is a significant problem for the development of every country in the world. ASEAN countries tend to have high unemployment rates and middle-income. The research we conducted has the main objective, namely to analyze what factors cause elevated levels of unemployment in the population of 6 ASEAN countries, namely (Indonesia, Philippines, Laos, Malaysia, Vietnam, and Thailand) which still have high unemployment rates. The analysis period that we carried out was from 2008 to 2022. This research found that the economic growth variable had a negative and insignificant influence. In contrast, the population number 15-64 years variable had a positive and significant influence, and the Foreign direct investment variable negatively and significantly influenced total unemployment in ASEAN-6.